Galaxy And Mass Assembly: the G02 field, Herschel–ATLAS target selection and data release 3. Issue 3 (24th November 2017) - Baldry, I K; Liske, J; Brown, M J I; Robotham, A S G; Driver, S P; Dunne, L; Alpaslan, M; Brough, S; Cluver, M E; Eardley, E; Farrow, D J; Heymans, C; et al.
Abstract: We describe data release 3 (DR3) of the Galaxy And Mass Assembly (GAMA) survey. The GAMA survey is a spectroscopic redshift and multiwavelength photometric survey in three equatorial regions each of 60.0 deg 2 (G09, G12, and G15), and two southern regions of 55.7 deg 2 (G02) and 50.6 deg 2 (G23). DR3 consists of: the first release of data covering the G02 region and of data on H-ATLAS (Herschel – Astrophysical Terahertz Large Area Survey) sources in the equatorial regions; and updates to data on sources released in DR2. DR3 includes 154 809 sources with secure redshifts across four regions. A subset of the G02 region is 95.5 per cent redshift complete to r < 19.8 mag over an area of 19.5 deg 2, with 20 086 galaxy redshifts, that overlaps substantially with the XXL survey (X-ray) and VIPERS (redshift survey). In the equatorial regions, the main survey has even higher completeness (98.5 per cent), and spectra for about 75 per cent of H-ATLAS filler targets were also obtained. This filler sample extends spectroscopic redshifts, for probable optical counterparts to H-ATLAS submillimetre sources, to 0.8 mag deeper ( r < 20.6 mag) than the GAMA main survey. There are 25 814 galaxy redshifts for H-ATLAS sources from the GAMA main or filler surveys. GAMA DR3 is available at the survey website (www.gama-survey.org/dr3/ ).